Effect of tert-Butylhydroquinone on the Oxidative Stability and Storage Quality of Tabak-Maz, a Kashmiri Meat Product - Dua, Sourab; Bhat, Z. F.; Kumar, Sunil (Journal of Meat Science, 2015)
The study was conducted to evaluate the effect of tert-Butylhydroquinone (TBHQ) on the oxidative stability and storage quality of Tabaq-Maz, a popular traditional meat product of Wazwan-the cuisine of indigenous meat products of Kashmir. The products were prepared and treated with TBHQ (200 ppm) and were aerobically packaged and assessed for lipid stability and storage quality parameters under refrigerated (4±10C) conditions. TBHQ showed a significant (p
Keywords: Tabak-Maz; Mutton; TBHQ; Lipid stability; Storage quality